Carrageenan bionanocomposite films incorporating Ag and Zn-Doped CeO₂ nanoparticles for active food packaging applications - Damar Rastri Adhika; Gita Genecya; Alvin Annayya Habibah; An Naas Amalia Rahardja Putri; Ubed Sonai Fahruddin Arrozi (OpenNano)
The increasing demand for sustainable and safe food packaging has led to the exploration of bio-based materials and advanced packaging technologies. This study investigates the incorporation of silver (Ag) and zinc (Zn) doped cerium oxide nanoparticles (CeO₂ NPs) into carrageenan-based bionanocomposite films to enhance their antimicrobial properties, mechanical strength, and hydrophobicity. The synthesis of CeO₂ NPs, doped with varying concentrations of Ag and Zn, was achieved using the green synthesis method with green tea extract as a reducing agent. Characterization techniques such as X-ray diffraction (XRD), transmission electron microscopy (TEM), and Zeta potential analysis confirmed the successful doping and stability of the nanoparticles. The bionanocomposites were evaluated for their mechanical properties, water contact angle, and antibacterial activity against Escherichia coli and Bacillus cereus. Mechanical testing revealed that the addition of CeO₂ NPs, particularly Ag-doped CeO₂ NPs, significantly improved the tensile strength and Young's modulus of the bionanocomposites. Hydrophobicity assessments showed that Zn-doped CeO₂ NPs enhanced water resistance compared to Ag-doped CeO₂ NPs, making them more suitable for food packaging applications. Zn and Ag-doped CeO₂ NPs exhibited superior antibacterial activity compared to undoped CeO₂ NPs, with 20 wt% Ag-doped NPs showing the highest antibacterial activity compared to Amoxicillin as positive control and other variations. The study concludes that Zn and Ag-doped CeO₂ NPs are promising additives for developing effective and sustainable active food packaging materials.